Defining the criteria for identifying constitutional epimutations. Issue 1 (December 2016) - Sloane, Mathew; Ward, Robyn; Hesson, Luke
Abstract In the January 2016 issue ofClinical Epigenetics, Quiñonez-Silva et al. (Clin Epigenetics 8:1, 2016) described a possible constitutional epimutation of theRB1 gene as a cause of hereditary predisposition to retinoblastoma. The term constitutional epimutation describes an epigenetic aberration in normal tissues that predisposes to disease. The data presented by Quiñonez-Silva et al. are interesting, but further analysis is required to demonstrate a constitutional epimutation in this family. Here, we define the criteria and describe the experimental approach necessary to identify an epigenetic aberration as a constitutional epimutation.